Kontekstualisasi Pemahaman Hadis tentang Keutamaan Membunuh Tokek - Budiman, Arif (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This article analyzes the hadith about the Prophet's order to kill a lizard. If at a glance, this hadist seems contradictory to Q.S: Al-A'raf: 56 that is the prohibition of damaging natural balance. In terms of the command to kill animals is one of the forms of devastation. Meanwhile, the facts of science show that lizards are useful in alternative medicine. Thus, the editor of hadist seems contrary to the verses of the Qur'an and scientific facts. The settlement is carried out by taking step of the research method of Thematic Hadist (maudhu'iy). The author compiles data from various canonical and non-canonical hadist book. As a result, it has three variants. First, it is explain the order of killing lizards. Second, it explains the quantity of reward for killing lizards (wazagh). Third, it contains information that lizards (wazagh) is a nasty animal, which means an animal that is bothersome and hostile to humans.The scholars of Hadist states this hadist can be practiced, because the law is suppressed by hadist’s validity of killing 5 nasty animals. However, a review of the health and medical aspects, it shows that the lizard is beneficial for curing certain diseases. If the lizard is killed with the reason that has been stated by the scholars that it is killed because the animal is in vain, then the understanding is no longer relevant in the present. So that, a more precise understanding is to look at the hadith's essential inspiration that the Prophet SAW states